ECO-FRIENDLY CONCRETE: MERGING FLY ASH AND HEMP FOR GREEN BUILDING PRACTICES - Wajeeha Arshad; Nijah Akram; Ar. Saud Kamal; Muti ul Haq; Ar. Mirza Muhammad Khurshid; Ar. Arsalan Qayyum (Spectrum of Engineering Sciences, 2025)
The global construction industry significantly contributes to greenhouse gas emissions, highlighting the urgent need for innovative and environmentally beneficial building materials. This study presents Fly Ash Hemp Concrete (FAHC), a novel and eco-friendly alternative to traditional concrete. FAHC is an impressive combination of hemp shives, a widely available renewable natural fiber, fly ash, a useful byproduct of burning coal, and a lime-like binding substance. This cutting-edge composite material offers superior durability and thermal insulation while drastically reducing carbon emissions. Fly ash greatly enhances the workability and compressive strength of hempcrete. Additionally, it promotes carbonation, which effectively retains CO2 within the structure for its entire lifespan. Studies indicate that the optimal amounts of fly ash yield remarkable mechanical properties, establishing FAHC as a strong choice for sustainable construction. This study advances FAHC as a revolutionary solution for environmentally conscious building practices by leveraging the synergistic properties of fly ash and hemp, aligning the building sector with essential sustainability goals and paving the way for a more sustainable future.